Optimization of Protease Production by Streptomyces SP. LCJ1A Using Response Surface Methodology: Life Sciences-Microbiology for health care - Dhavala Swarna; J. Joel Gnanadoss (International Journal of Life Science and Pharma Research, 2022)
Protease is an industrially important enzyme obtained from plants and animals. Production of high amounts of protease at low cost is necessary for its use in different commercial applications. The main objective of this work was to formulate a suitable medium and to optimize various parameters for protease production by Streptomyces sp. LCJ1A which was isolated from Pichavaram mangroves, Tamil Nadu, India. The organism was quantitatively and qualitatively screened for protease production. Sequencing of 16S rRNA was done and the sequence was deposited in NCBI and Accession no. KU 870428 was obtained. For optimization, the conventional one-time factor method followed by the Plackett-Burman design was used to optimize various media components. Variables with a significant influence on the production of protease have been identified. Variables such as maltose, peptone, pH and temperature have shown its strong impact on protease production and the ideal concentration of these factors was further investigated by Response Surface Methodology. The Optimum values of tested variables for favourable protease production were: Maltose, peptone, pH and temperature. Further, the interaction effects of maltose and peptone were found to be extremely important suggesting that both components were extremely crucial for protease production. 186.92 U/mL of protease enzyme was obtained in the experimental study which was close to the predicted value of 190.67 U/mL, which could validate the model. Using such optimized variables, the protease production was increased by 10 times when compared with the unoptimized medium. This is the first report on the conventional and statistical optimization of protease production from Streptomyces sp. LCJ1A. This study also showed that statistical methods are indeed a better approach for optimization of media, when compared with conventional one- factor-at-a-time method in terms of an enhanced protease yield in a short time